Pemberdayaan Yayasan Sehati Bali Melalui Digital Marketing dan Komputerisasi Pencatatan Akuntansi - I Gusti Agung Ayu Mas Suariedewi; Ida Ayu Trisna Yudi Asri; Kadek Diviariesty (Universitas Warmadewa, 2024)
The partner in implementing PkM is located at the Yayasan Sehati Bali North Denpasar District. The target of this community service is managers who will be given training by the implementation team. The background to the implementation of this activity is due to social media content being less than informative and understanding of digital marketing not being optimal and not yet understanding the computerized accounting cycle of financial transactions. The aim of this training is so that Yayasan Sehati Bali managers can manage social media content more interestingly and effectively and partners are able to carry out computerized accounting records with modifications to Microsoft Excel. Implementation of activities is provided in the form of training using socialization methods regarding the importance of implementing digital marketing and computerization in accounting records for foundations since their inception. Coaching is accompanied by helping create content for marketing on social media platforms and introducing several applications or social media that can be used to promote the foundation easily. Apart from that, training will be provided in carrying out accounting records using simple Microsoft Excel to help foundations in carrying out neat accounting records. So that administrators are expected to be able to carry out promotions and administrative records, especially in accounting, better. The output target to be achieved is improving social media content management skills and accounting records by Yayasan Sehati Bali.